Childhood maltreatment and metabolic syndrome in bipolar disorders: In search of moderators. (September 2021) - Godin, Ophelia; Gaube, Géraud; Olié, Emilie; Belzeaux, Raoul; Bellivier, Frank; Loftus, Joséphine; Courtet, Philippe; Dubertret, Caroline; llorca, Pierre-Michel; Gard, Sebastien; Henry, Chantal; Schwan, Raymund; et al.
Abstract: As compared to the general population, adult individuals with bipolar disorders (BD) have higher mortality rates due to cardiovascular diseases and higher prevalence of Metabolic Syndrome (MetS). Recent evidence suggests that childhood maltreatment may contribute to the cardiovascular burden in individuals with BD. However, studies are scarce, with limited sample sizes and inconsistent results. We explored the associations between a self-reported history of childhood maltreatment and MetS (and its subcomponents) in a large sample of 2390 individuals with BD. Childhood maltreatment was assessed using the Childhood Trauma Questionnaire and MetS was defined according to the revised criteria of the ATEP III. We suggested associations between childhood maltreatment and the presence of MetS in men and in younger individuals. The association between childhood maltreatment and the presence of MetS in the early onset subgroup was not significant after adjustment for site of recruitment and level of education. Hence, some links between childhood maltreatment and MetS might exist only in specific subgroups of individuals with BD, but confirmation is required in independent and large samples, while taking into account potential confounders. This would help defining how psychosocial interventions that target childhood maltreatment and its consequences may be beneficial for physical health. Highlights: Childhood maltreatment does not strongly influence MetS or its components. However, links between childhood maltreatment and MetS might exist in specific subgroups (males, younger individuals). Benefits of psychosocial interventions targeting the consequences of childhood trauma on physical health should be evaluated.